Synergy between CD40 and MyD88 does not influence host survival to Salmonella infection - Wenzel, Ulf A.; Fernandez-Santoscoy, Maria; Tam, Miguel A.; Tegtmeyer, Pia; Wick, Mary Jo (Frontiers in Immunology, 2015)
Previous studies using purified TLR ligands plus agonistic anti-CD40 antibodies showed that TLRs and CD40 can act synergistically on dendritic cells (DCs) to optimize T cell activation and Th1 differentiation. However, a synergistic effect of TLRs and CD40 during bacterial infection is not known. Here we show that mice lacking the TLR adaptor MyD88 alone, or lacking both MyD88 and CD40 (DKO mice), are compromised in survival to Salmonella infection but have intact recruitment of neutrophils and inflammatory monocytes as well as unaltered abundance of DC subsets and DC activation in infected tissues. In contrast to infected wildtype and CD40-/- mice, both MyD88-/- mice and DKO mice lack detectable serum IFN-γ and have elevated IL-10. A synergistic effect of TLRs and CD40 was revealed in co-culture experiments where OT-II T cell proliferation was compromised when DKO DCs were pulsed with OVA protein and OVA323-339 peptide, but not with heat-killed Salmonella expressing OVA (HKSOVA), relative to MyD88-/- DCs. In contrast, MyD88-/- or DKO DCs pulsed with any of the antigens had a similar ability to induce IFN-γ that was lower than WT or CD40-/- DCs. DKO DCs pulsed with HKSOVA, but not with OVA or OVA323-339, had increased IL-10 relative to MyD88-/- DCs. Finally, HKSOVA-pulsed MyD88-/- and DKO DCs had similar and low induction of NFκB- dependent and -independent genes upon co-culture with OT-II cells. Overall, our data revealed that synergistic effects of CD40 and MyD88 do not influence host survival to Salmonella infection or serum levels of IFN-γ or IL-10. However, synergistic effects of MyD88 and CD40 may be apparent on some (IL-10 production) but not all (OT-II proliferation and IFN-γ production) DC functions and depend on the complexity of the antigen. Indeed, synergistic effects observed using purified ligands and well-defined antigens may not necessarily apply when complex antigens, such as live bacteria, challenge the immune system.